Determinants of Resistance to Changes in Hospital Program Implementation - Rusmawati, Aprin; Wardani, Ratna; Fajriah, Asruria Sani (Journal of Health Policy and Management, 2021)
Background: Organizational change is the embodiment of changing organizational environments, structures, cultures, technologies, or people. Changes are planned to make the organization more effective and efficient, but there is still resistance from members of the organization. Negative reactions arise because changes provide pressure, stress, and uncertainty for employees. The goal in the study was to analyze employees' perceptions of commitment, readiness, and resistance during times of change to the implementation of the "MARMER" program.Subjects and Method: The study was conducted at Dr. Iskak Tulungagung Hospital. The selected hospital organization is a hospital that has a program preventing antimicrobial resistance through restriction efficiency (MARMER) for the control of antibiotic resistance. Research design uses quantitative research methods. The population in this study is all health workers at Dr. Iskak Tulungagung Hospital. Data collection through questionnaires. Multivariate data analysis using SEM with SmartPLS.Results: Commitment to change has a significant direct influence on the readiness for change (t-values= 9.95 > 1.96; Standard Coefficiency= 0.53). Commitment to change does not significantly affect change resistance (t-values = 1.22< 1.96; Standard Coefficiency= 0.13). Readiness for change has a negative effect on change resistance (t-values= -5.30 >1.96; Standard Coefficiency= -0.60). Commitment to change negatively and significantly affects resistance to change through readiness to change (t-values = -4.24 > 1.96; Standard Coefficiency= -0.36).Conclusion: Commitment directly affects the readiness of change. Commitment and readiness affect the resistance of change. Commitment has a significant effect on resistance through readiness for change.Keywords: MARMER, antibiotik, commitment, readiness, resistanceCorrespondence: Asruria Sani Fajriah, IIK Strada Indonesia, Jl. Manila 37, Sumberece, Kediri, East Java, Indonesia. Email: sanifajriah@gmail.comJournal of Health Policy and Management (2021), 06(03): 222-232https://doi.org/10.26911/thejhpm.2021.06.03.07